2000
DOI: 10.1086/312778
|View full text |Cite
|
Sign up to set email alerts
|

Time Domain Analysis of Variability in Cygnus X-1: Constraints on the Emission Models

Abstract: We use time domain analysis techniques to investigate the rapid variability of Cygnus X-1. We show that the cross-correlation functions between hard and soft energy bands reach values very close to unity and peak at a lag of less than 2 ms for energies separated by a factor of 10. This confirms that the process that produces Xray photons at different energies is extremely coherent on short timescales and strongly constrains emission models proposed to explain Fourier-frequency-dependent time lags. We present a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
84
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(108 citation statements)
references
References 23 publications
(37 reference statements)
22
84
2
Order By: Relevance
“…Recent RXTE observations (Maccarone, Coppi, & Poutanen 2000) clearly show asymmetries of the CCFs, which, however, peak within ∼ 1 ms from zero lag (see Fig. 2).…”
Section: Variability In the Time Domain Auto-and Cross-correlation Fumentioning
confidence: 86%
“…Recent RXTE observations (Maccarone, Coppi, & Poutanen 2000) clearly show asymmetries of the CCFs, which, however, peak within ∼ 1 ms from zero lag (see Fig. 2).…”
Section: Variability In the Time Domain Auto-and Cross-correlation Fumentioning
confidence: 86%
“…Similar to Maccarone et al (2000), we computed the autocorrelation function in three energy bands: 20-50 keV of SuperAGILE, 1.5-5 keV given by the sum of the A and B bands of RXTE/ASM and 5-12 keV from the ASM C band. Apart from the peak at zero lag, no other peak is found, indicating that the source emission does not show periodicity in all energy ranges.…”
Section: Alternative Methods Of Timing Analysismentioning
confidence: 99%
“…With this modification we are able to explain two additional observational facts exhibited by Cygnus X-1. One is the narrowing of the autocorrelation function with increasing photon energy (Maccarone et al 2000) and the other is the hardening of the high-frequency power spectrum with increasing photon energy (Nowak et al 1999). Preliminary results of this work appeared in Kylafis et al (2004).…”
Section: Introductionmentioning
confidence: 68%
“…In the context of our model, this can be understood as the association of the state transitions with a more extended jet. Maccarone et al (2000) computed the autocorrelation functions (ACF) of the light curves of Cygnus X-1 in different energy bands and showed that the width of the ACF decreases with photon energy. This imposes strong constraints on the different models that attempt to describe both the spectral and the temporal properties of accreting black-hole binaries.…”
Section: Energy and Time-lag Spectramentioning
confidence: 99%
See 1 more Smart Citation